Summer and Autumn Movements and Habitat Use by Belugas in the Canadian High Arctic and Adjacent Areas - Richard, P.R.; Heide-Jørgensen, M.P.; Orr, J.R.; Dietz, R.; Smith, T.G. (ARCTIC, 2001)
Twenty-one adult belugas (8M, 13F) were live-captured and instrumented with satellite-linked transmitters in the summer and fall of 1996. Twelve were captured in estuaries along the coast of Somerset Island in July and nine were captured in September in Croker Bay, SE Devon Island. This paper reports on the summer and autumn movements and dive depths of these animals from late July 1996 until the last tags ceased transmitting in November 1996. Of the 12 captured in July, 11 provided data for 30-126 days (mean = 84 days). Most of the animals moved rapidly to southern Peel Sound, where they all spent the month of August, making frequent deep dives, some of which were to depths near or at the seabed of the Franklin Trench. The belugas also used several bays along the coast of Prince of Wales Island and another one on Melville Peninsula. They left southern Peel Sound between late August and early September and moved rapidly to the south coast of Devon Island, many using Maxwell Bay and Croker Bay for several days. All belugas instrumented in Croker Bay in September, as well as the summer-tagged individuals that were still transmitting, moved east and north along the south and east coasts of Devon Island, eventually reaching Jones Sound and north Baffin Bay. They used many bays along the east coast of Devon Island and dove to depths often exceeding 200 m in the surrounding waters. Fifteen of the tags continued to transmit during the period when belugas are normally observed migrating along the West Greenland coast (late September-early October). Only one of the tagged animals moved to Greenland waters in late September. The others remained in the area known in winter as the North Water. The autumn tracking results suggest that the North Water may harbour a larger winter population of belugas than was previously suspected. Durant l'été et l'automne de 1996, on a capturé 21 bélugas adultes (8 mâles, 13 femelles), qu'on a équipés d'émetteurs-satellite. Douze d'entre eux ont été capturés en juillet dans des estuaires ...